THE ANTIMICROBIAL ACTIVITIES OF SCLEROCARYA BIRREA EXTRACTS AGAINST THREE STRAINS OF PATHOGENIC YEASTS - Mmushi, T. J.; Masoko, P.; Mogashoa, M.; Mokgotho, M. P.; Mampuru, L. J.; Howard, R. L. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Sclerocarya birrea is used by some of South African traditional healers for the treatment of skin disorders and epilepsy. The leaves, barks and roots of this plant were scientifically investigated for antifungal activity against Candida parapsilosis, Cryptococcus albidus and Rhodotorula mucilaginosa which are opportunistic and systemic skin pathogens. The phytochemical constituents of finely ground plant parts were extracted using four different solvents (hexane, dichloromethane, acetone and methanol). The phytochemical analysis, antioxidant activity and bioautography were evaluated on chromatograms separated by eluting systems, BEA (benzene: ethanol: ammonia), CEF (chloroform: ethyl acetate: formic acid) and EMW (ethyl acetate: methanol: water). The antifungal activities were tested against all organisms and extracts. Amphotericin B was used as the positive control. Methanol yielded the highest quantity of extracts while acetone had the highest antifungal activity. The phytochemical analysis revealed the presence of different compounds on the chromatograms. The eluting system BEA had the best separation for all extracts. Acetone, ethanol and methanolic bark extracts had the lowest MIC values of 0.16 mg/ml against all tested pathogens. All bark extracts extrated with non polar or intermediate polar solvents were not active. Polar extracts had high activity, high enough to consider for clinical application and for isolation and characterization of antifungal compounds. Acknowledgements: The National Research Foundation (NRF) and Department of Biochemistry, Microbiology and Biotechnology, University of Limpopo provided financial assistance.